2015
DOI: 10.1155/2015/903782
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Multidrug Resistance-Associated Protein 1 by Allyl Isothiocyanate in Human Bronchial Epithelial Cell: Involvement of c-Jun N-Terminal Kinase Signaling Pathway

Abstract: Multidrug resistance-associated protein 1 (MRP1) plays a protective role in the etiology and progression of chronic obstructive pulmonary disease (COPD) which results from oxidative stress and inflammation of lung injury. The lower functional MRP1 activity is related to COPD development. Our previous study showed that Allyl isothiocyanate (AITC) induced the expression and activity of MRP1 in a dose-dependent manner. However, which signaling pathway contributes to the upregulation of MRP1 by AITC is unclear. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…This upregulation was also functionally confirmed as the MRP1 substrate CFDA was effluxed in greater magnitude the more the cells were exposed to allyl isothiocyanate (5–40 μM). The authors connected the upregulation of MRP1 to the c‐Jun‐ N ‐terminal kinase (JNK) signaling pathway, as it could be reversed using the JNK inhibitor SP600125 (Figure ) . An increase in MRP1 expression was also observed for the isothiocyanate alyssin (10 μM; Figure ) in combination with either 250 μM verapamil or furosemide (Figure 37) .…”
Section: Natural Product Drugs and Synthetic Analogsmentioning
confidence: 97%
“…This upregulation was also functionally confirmed as the MRP1 substrate CFDA was effluxed in greater magnitude the more the cells were exposed to allyl isothiocyanate (5–40 μM). The authors connected the upregulation of MRP1 to the c‐Jun‐ N ‐terminal kinase (JNK) signaling pathway, as it could be reversed using the JNK inhibitor SP600125 (Figure ) . An increase in MRP1 expression was also observed for the isothiocyanate alyssin (10 μM; Figure ) in combination with either 250 μM verapamil or furosemide (Figure 37) .…”
Section: Natural Product Drugs and Synthetic Analogsmentioning
confidence: 97%
“…Rho-123 was a special substrate for P-gp which contains yellow-green fluorophores. CFDA was used as a model MRP1 substrate to evaluate the function of MRP1 (25).…”
Section: Multidrug Resistance Determination In K562/adm Cells Cellmentioning
confidence: 99%
“…The results were consistent with the previous study of our research group. Our previous results indicated that AITC upregulated the expression levels of MRP1 in 16HBE cells via the JNK signaling pathway in a concentration-dependent manner ( 15 , 16 ). MRP1 plays a protective role in the COPD process, whereas the JNK pathway also plays an important role in the treatment of COPD ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Benzyl-ITC and phenethyl isothiocyanate have been revealed to play an antitumor effect via regulation of the expression of MRP1( 14 ). Preliminary studies indicated that AITC increased the expression and activity of MRP1 in 16HBE14o-cells in a concentration-dependent manner via the JNK signaling pathway ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%